1999
DOI: 10.1021/ma981353+
|View full text |Cite
|
Sign up to set email alerts
|

Radical Polymerization Initiated from a Solid Substrate. 1. Theoretical Background

Abstract: From a survey of the literature on grafting free radical polymerization from solid surfaces we suggest kinetic schemes for the process. The system of differential equations in partial derivatives including the diffusion equation based on the classical theory of free radical polymerization and the assumption that surface-bonded free radicals terminate by (1) reactions with bulk free radicals and (2) chain transfer to solvent or monomer are introduced. Computer simulations performed using the equations have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 16 publications
0
40
0
2
Order By: Relevance
“…A solution of tert-butyl hydroperoxide (10.8 g, 0.12 mol) in diethyl ether (30 mL) was added dropwise to a suspension of N-(hydroxymethyl)acrylamide (10.1 g, 0.1 mol) in diethyl ether (25 mL) at 5-7 C. The mixture was stirred and a solution of H 2 SO 4 (2.94 g, 0.03 mol) in diethyl ether (20 mL) was added for 1 h at [14][15][16] C. After stirring for additional 3 h at [22][23][24][25] C, the organic phase was separated, washed in series with water, 5% aq Na 2 CO 3 , and water until pH 7. The organic phase was dried over MgSO 4 Polyacrylamide A solution of acrylamide (100 g) and 2-propanol (10 or 30 g) in water (890 or 870 mL, respectively) was degassed with argon.…”
Section: N-(tert-butylperoxymethyl)acrylamide (Pm)mentioning
confidence: 99%
See 1 more Smart Citation
“…A solution of tert-butyl hydroperoxide (10.8 g, 0.12 mol) in diethyl ether (30 mL) was added dropwise to a suspension of N-(hydroxymethyl)acrylamide (10.1 g, 0.1 mol) in diethyl ether (25 mL) at 5-7 C. The mixture was stirred and a solution of H 2 SO 4 (2.94 g, 0.03 mol) in diethyl ether (20 mL) was added for 1 h at [14][15][16] C. After stirring for additional 3 h at [22][23][24][25] C, the organic phase was separated, washed in series with water, 5% aq Na 2 CO 3 , and water until pH 7. The organic phase was dried over MgSO 4 Polyacrylamide A solution of acrylamide (100 g) and 2-propanol (10 or 30 g) in water (890 or 870 mL, respectively) was degassed with argon.…”
Section: N-(tert-butylperoxymethyl)acrylamide (Pm)mentioning
confidence: 99%
“…13 It has been reported that peroxide groups immobilized on the surface of different mineral powders are widely used to initiate free radical polymerization from the solid surface. [13][14][15][16] A variety of polymeric [17][18][19] and low molecular weight peroxides 16,19,20 have been utilized for the initiation of grafting polymerization from the solid particulate surface, which results in the encapsulation of the powder particles because of the formation of a thin polymer layer on the dispersed surface. 21 The proposed approach is based on the formation of polyacrylamide (PAAm) hydrogels, with enhanced mechanical properties and regular pore distribution using silica particles with grafted polyacrylamide as a porogen and the subsequent leaching out of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Minko et al 42 discussed the theoretical background of the radical polymerization initiated from a solid substrate in which the initiator is attached to a solid surface: after a specific grafting time, the grafting surface is completely covered by polymer coils. The subsequent grafting of new chains requires stretching of the coils until the maximum possible surface grafting is obtained.…”
Section: ␥-Initiated Conventional and Raft-agent-mediated Free-radicamentioning
confidence: 99%
“…This “grafting to” approach provides rather low grafting densities of grafted polymers. The so‐called “grafting from” approach consists of attachment of the initiator to the substrate surface and the successive propagation of polymerization from the surface 11–13. This method assures high grafting density with more than 100‐nm‐thick brushes.…”
Section: Introductionmentioning
confidence: 99%